How to become successful teachers of the art of dancing, in conjunction with how to manage a favor-german - Grant, Horatio N. (Buffalo, N.Y. [Kraft & Stern, Printers], 1893)
Written for teachers of ballroom dance, this manual is illustrated with many diagrams designed to be useful in the classroom. Discussions include how to open a dance class, how to conduct a private lesson, and what to teach. Suggestions on appropriate dances include the mazurka, redowa, and polka. Group dances include descriptions of several figures for the grand march, six figures for the German (also known as the cotillon), and several contra dances.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Dance -- Study and teaching; Dance Instruction and Physical Culture